Physiotherapy Management in Spina Bifida Cases - Riantini, Ni Putu; Rahayu, Umi Budi; Waspada, Edy (Universitas Muhammadiyah Surakarta, 2023)
Spina bifida or neural tube defect (NTD) is a spinal disorder that does not close completely, resulting in disability or developmental failure of the spinal cord. The cause of spina bifida has no definite reason, but there are several factors that are considered to increase the risk, namely folic acid deficiency, family history of spina bifida, and history of taking drugs. Patients with spina bifida will experience weakness in the lower extremity muscles, decreased ability to control urination, and decreased ability to carry out daily activities. The study used a case report study conducted at YPAC Surakarta for boys aged 15 years with spina bifida disorder. Physiotherapy plays a role in optimizing muscle strength, active movement of children, and improving functional abilities by using interventional stretching exercises, myofacial release, strengthening exercises, and a combination of Kegel Exercises and bridging exercises. After being treated for 6 times T1-T6 there was an increase in muscle strength as measured by manual muscle testing (MMT), changes in the range of motion of the joints (LGS) as measured by the goniometer, an increase in functional ability as measured by the Barthel Index.